Position epistemological, paradigmatical and pedagogical of the curriculum for the Degree in Nursing at the University of Costa Rica - Leiva Díaz, Viriam (2013)
We present the results of educational research which analyzed the epistemological position, paradigmaticand educational curriculum of the Degree of Nursing at the University of Costa Rica. The population consisted ofthe graduates of the School of Nursing. For the participation of teachers in service, worked with saturation (11).For graduates (2008) the population was 74 for a sample of 47 of them and her. We analyzed three dimensions theepistemological and pedagogical paradigm of teaching and reflected in the curriculum. To collect data, aquestionnaire was structured and semi-structured interviews to selected population. The study found that althoughthe position does not require explicit epistemic quote, there are some modules that need internal review to showconsistency between what is manifested mainly in learning activities and methodology, with the characteristicsand assumptions of the hermeneutic interpretive position curriculum. Moreover we can consider that the modulesdespite their particularities and differences in their teaching and learning, with characteristics savedapproximation pedagogical approach that suggests the curriculum. We conclude that it is not explicit or clear theposition that the teachers expressed regarding the pedagogical approach of the curriculum, so it is essential todeepen these concepts again with faculty. However, it is clear that significant progress has been made, howeverthey must think that the investigation is unrelated to the nursing task, a finding consistent with the findings 12years ago, when he became the curriculum change.